Computational model of intraluminal thrombus growth in abdominal aortic aneurysms with fibrin generation - Taylor, Mark Robin (Department of Mechanical Engineering, 2021)
Abdominal aortic aneurysms affect 0.2% of the population and are closely associated with intraluminal thromboses (ILTs) that develop in the sac. Advanced imaging and treatment techniques are available, however there is room for improvement in the methods used to predict the outcome or necessity of surgical intervention. For a computational model to be useful in this clinical setting, it would need to incorporate relevant patient-specific data and prioritise simplicity and speed over exhaustive detail. This paper presents the details of such a model, for abdominal aortic aneurysms, particularly in the simplification of the coagulation biochemistry. Explicit modelling of the coagulation cascade is replaced with a patient-specific thrombin generation curve. This curve is defined by three values obtained from a blood test. Another key feature is the thrombosis growth model, which incorporates conversion of fibrinogen to fibrin, variation between clot core and shell, and mechanical lysis. The model generates ILTs with morphologies visually similar to those typically found in the body, however more work is required to refine and validate the mode.